2013
DOI: 10.3354/ab00527
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ocean acidification and global warming on reef bioerosion—lessons from a clionaid sponge

Abstract: Coral reefs are under threat, exerted by a number of interacting effects inherent to the present climate change, including ocean acidification and global warming. Bioerosion drives reef degradation by recycling carbonate skeletal material and is an important but understudied factor in this context. Twelve different combinations of p CO 2 and temperature were applied to elucidate the consequences of ocean acidification and global warming on the physiological response and bioerosion rates of the zooxanthellate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
86
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(97 citation statements)
references
References 58 publications
9
86
2
Order By: Relevance
“…Results regarding higher rates at increased pCO 2 are comparable to previous studies on other clionaid species (C. orientalis and C. celata) (Wisshak et al, 2012(Wisshak et al, , 2013(Wisshak et al, , 2014Fang et al, 2013a). Sponges and other borers are assumed to benefit from eutrophication (Holmes, 2000;Carballo et al, 2008).…”
Section: Effects Of Pco 2 and Eutrophication On Bioerosionsupporting
confidence: 77%
See 3 more Smart Citations
“…Results regarding higher rates at increased pCO 2 are comparable to previous studies on other clionaid species (C. orientalis and C. celata) (Wisshak et al, 2012(Wisshak et al, , 2013(Wisshak et al, , 2014Fang et al, 2013a). Sponges and other borers are assumed to benefit from eutrophication (Holmes, 2000;Carballo et al, 2008).…”
Section: Effects Of Pco 2 and Eutrophication On Bioerosionsupporting
confidence: 77%
“…Therefore, the sum of chemical and mechanical bioerosion should be considered as being conservative. Here, total bioerosion rates yielded from buoyant weight measurements are regarded as more reliable and are comparable to results estimated from previous studies (Fang et al, 2013a;Wisshak et al, 2013). Rates of chip production did not differ significantly between pCO 2 scenarios, day/night and eutrophication treatments.…”
Section: Effects Of Pco 2 and Eutrophication On Bioerosionsupporting
confidence: 72%
See 2 more Smart Citations
“…Rützler and Rieger 1973;Zundelevich et al 2007;Nava and Carballo 2008;see Wisshak et al 2013 for an overview), we proposed that it is mainly the chemical dissolution which is sensitive to ambient pH and will thus be accelerated in a more acidic environment . The rate of mechanical extraction of sponge chips, however, remains relatively constant in case of C. orientalis (figure 7 in Wisshak et al 2013). This line of reasoning was supported most recently by Fang et al (2013) who found a significant increase in chemical, but stable mechanical sponge bioerosion rates under a series of combined acidification and warming scenarios.…”
Section: Introductionmentioning
confidence: 99%